2003
DOI: 10.1051/forest:2003031
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of crown radii and crown projection area from stem size and tree position

Abstract: -This paper describes a method for crown radii estimation in different cardinal directions using tree diameter, height, crown length, and stem position within the stand as independent variables. The approach can serve for the initialisation of crown dimensions if measured crown radii are not available in order to address various research questions. Test calculations are carried out with 4 pure spruce (Picea abies L. Karst), 5 beech (Fagus sylvatica L.), and 6 mixed stands with both species. Simulated tree radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 35 publications
2
34
0
3
Order By: Relevance
“…We have focused on obtaining a good spatial distribution of the total crown volume at a local scale and have not validated our approach by directly comparing modelled crowns to real ones, and only tested if the simulated stands with reconstructed crowns gave good results in the light model. An approach similar to the CROM algorithm has been proposed by Grote [32] in which potential crown radius is predicted from stem diameter without using crown volume, and by managing overlaps in a simpler way than in the CROM algorithm. In this work, validation is made in terms of crown geometry and shows a strong correlation of crown projection areas with measured ones but poor prediction for particular radii.…”
Section: Discussionmentioning
confidence: 99%
“…We have focused on obtaining a good spatial distribution of the total crown volume at a local scale and have not validated our approach by directly comparing modelled crowns to real ones, and only tested if the simulated stands with reconstructed crowns gave good results in the light model. An approach similar to the CROM algorithm has been proposed by Grote [32] in which potential crown radius is predicted from stem diameter without using crown volume, and by managing overlaps in a simpler way than in the CROM algorithm. In this work, validation is made in terms of crown geometry and shows a strong correlation of crown projection areas with measured ones but poor prediction for particular radii.…”
Section: Discussionmentioning
confidence: 99%
“…With an estimated maximum diameter of the fine root system of 20 m (Carpinus and Tilia) to 40 m (Fagus and Acer), trees of these species may spread their fine roots over an area of ca. 300 m 2 and up to 1,200 m 2 , which is roughly 5-20 times the size of the corresponding crown projection area (Frech et al 2003;Utschig and Küsters 2003;Grote 2003;Hemery et al 2005;Frech 2006). While Hölscher et al (2002) found a maximum horizontal extension of only ca.…”
Section: Horizontal Fine Root Distribution and Species Overlapmentioning
confidence: 99%
“…Nowadays, allometric models are a common method for the estimation of CPA based on easily measurable proxy variables like basal area (BA) [30].…”
Section: Allometric Modelsmentioning
confidence: 99%
“…• , and 315 • ) were measured for a total of 132 trees located in the center of the stand using the "tangential-look-up-method" (tangentiale Hochblickmethode) [13,30] in winter 2016/17. Crown radii measurements were independently repeated by three persons to assess possible inter-observer bias.…”
Section: Data Collectionmentioning
confidence: 99%